2020
DOI: 10.1002/ctm2.139
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of metastatic traits via miR‐200c in extracellular vesicles derived from colorectal cancer stem cells is inhibited by atractylenolide I

Abstract: Cancer stem cells (CSCs) are important factors contributing to tumorigenesis. We examined whether CSCs isolated from colorectal cancer (CRC) cells possess metastatic properties that can be transferred to non‐CSCs via the delivery of miR‐200c enclosed in extracellular vesicles (EVs). The inhibitory effect of atractylenolide I (ATL‐1), a traditional Chinese medicinal compound, on miR‐200c activity and metastatic transfer was investigated. EVs were isolated from colorectal CSCs. The expression of miR‐200c was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Extensive research has revealed that EVs are widely spread and can steadily exist in various body fluids including plasma, milk, and saliva [ 8 , 9 ]. Easy access to EVs and its wide existence ensure EVs to be a potent biomarker and imply its regulatory roles in diseases including tumors, autoimmune and inflammatory diseases [ 10 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has revealed that EVs are widely spread and can steadily exist in various body fluids including plasma, milk, and saliva [ 8 , 9 ]. Easy access to EVs and its wide existence ensure EVs to be a potent biomarker and imply its regulatory roles in diseases including tumors, autoimmune and inflammatory diseases [ 10 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with our observations, a previous study reported that exosomes derived from 5-fluorouracil-resistant cells transferred p-STAT3 and conferred drug resistance to drug-sensitive cells [ 81 ]. Other studies demonstrated the extracellular vesicle/exosome-mediated metastatic properties of the bladder [ 64 ] and colorectal [ 82 ] cancers. Our findings partially elucidated the mechanism through which GSCs confer stemness and invasive properties to non-GSCs by cargo conveyer of oncogenic Akt, mTOR, PI3K, and activated STAT3 (p-STAT3).…”
Section: Discussionmentioning
confidence: 99%
“…The main role of EVs also includes their fusion with macrophages and other immune cells [ 30 , 31 ]. CSCs and their EVs are able to modulate cancer cell proliferation by the release of proteins [ 44 , 45 , 46 ] and miRNAs [ 30 , 47 , 48 , 49 , 50 , 51 ]. Examples are increasing, with results in favor or against cancer.…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%
“…The first of these are in favor. The miR-92/PD-L1 pathway contributes to the suppression of immune cell function [ 30 ] and miR-200c stimulates the metastatic traits in colorectal cancer [ 47 ]. On the other hand, human liver cancer is attenuated in vitro and in vivo by miR-145 and miR-200 [ 48 ]; inhibition of lung metastasis is induced in osteosarcoma by miR-101 [ 49 ]; miR-8063 inhibits self renewal of GSC [ 50 ]; miR-663 inhibits the CSCs of a glioma [ 51 ]; and miR-1468-5p promotes a tumor immune escape [ 52 ].…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%
See 1 more Smart Citation